2021
DOI: 10.21608/arcs.2021.71826.1013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Accelerated Laboratory Ageing Factors on Linen Textiles Dyed with Turmeric Dye

Abstract: The effect of thermal and light aging processes on the mechanical, physical and chemical properties of dyed linen textiles.• The effect of light aging processes was greater on the mechanical properties of the dyed fibers. • The effect of ultraviolet radiation and heat on the morphological and chemical composition of dyed flax fibers ARTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Instrument was configured with ATR sample cell including a diamond crystal with a scanning depth up to 2 micrometers. The spectrum was recorded using the absorption method over a spectral range of 400-4000 cm -1 with an accuracy of 4 cm -1 [5,11,12,21].…”
Section: Attenuated Total Reflection -Fourier Transform Infrared Spec...mentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument was configured with ATR sample cell including a diamond crystal with a scanning depth up to 2 micrometers. The spectrum was recorded using the absorption method over a spectral range of 400-4000 cm -1 with an accuracy of 4 cm -1 [5,11,12,21].…”
Section: Attenuated Total Reflection -Fourier Transform Infrared Spec...mentioning
confidence: 99%
“…[1,2] Conservation processes comprise cleaning, disinfection, consolidation, and storage. [3][4][5] In the past, the process of conservation of archaeological textiles was carried out without following any scientific rules. It was done by sewing or by methods similar to household washing.…”
Section: Introductionmentioning
confidence: 99%
“…For the dyeing process, a percentage of the solution that was previously filtered from Madder Roots was used (a bath volume of 20 ml was used, per 1 gram of the dye), then the linen fibers that had been previously boiled well and rinsed to remove any sizing materials were dyed. After dyeing, the dye residue was removed by rinsing three times with cold water (5 min, at room temperature) [11,12].…”
Section: Linen Sample Dyeing Stagementioning
confidence: 99%
“…Colour change under light is a common problem in printing, 15,16 but it also occurs in other fields. [17][18][19] The colour fastness of printed products has been the subject of a number of studies, [20][21][22] in which the influence of the printing ink composition or printing process on colour light fastness was investigated. Additionally, prior research 23,24 showed possible protection of the print during accelerated ageing (AcA) with the use of nanocomposites, although this introduces higher costs and a more complex production process.…”
Section: Introductionmentioning
confidence: 99%
“…The protective role of varnishing is primarily in the mechanical area, to protect inks from rubbing or abrasion (scratching), but packaging is always influenced by electromagnetic radiation when packaged products are displayed on a shelf. Colour change under light is a common problem in printing, 15,16 but it also occurs in other fields 17–19 . The colour fastness of printed products has been the subject of a number of studies, 20–22 in which the influence of the printing ink composition or printing process on colour light fastness was investigated.…”
Section: Introductionmentioning
confidence: 99%